Suberoylanilide Hydroxamic Acid (SAHA) Treatment Reveals Crosstalk Among Proteome, Phosphoproteome, and Acetylome in Nasopharyngeal Carcinoma Cells - Huang, Huichao; Fu, Ying; Duan, Yankun; Zhang, Ye; Lu, Miaolong; Chen, Zhuchu; Li, Maoyu; Chen, Yongheng (Frontiers in Genetics, 2022)
Suberoylanilide hydroxamic acid (SAHA), as a famous histone deacetylase (HDAC) inhibitor, has been utilized in clinical treatment for cutaneous T-cell lymphoma. Previously the mechanisms underlying SAHA anti-tumor mainly focused on acetylome. However, the characteristics of SAHA in terms of other protein posttranslational modifications (PTMs) and the crosstalk between various modifications are poorly understood. Our previous work revealed that SAHA had the anti-tumor activity in nasopharyngeal carcinoma (NPC) cells as well. Here we reported that the profiles of global proteome, acetylome and phosphoproteome of 5-8F cells upon SAHA induction and the crosstalk between these data sets. Overall, we detected and quantified 6491 proteins, 2456 phosphorylated proteins and 228 acetylated proteins toward SAHA treatment in 5-8F cells. In addition, we identified 46 proteins exhibiting both acetylation and phosphorylation, such as WSTF and LMNA. With the aid of intensive bioinformatics analyses, multiple cellular processes and signaling pathways involved in tumorigenesis were clustered, including glycolysis, EGFR signaling and Myc signaling pathways. Taken together, this study highlighted the interconnectivity of acetylation and phosphorylation signaling networks and suggested SAHA-mediated HDAC inhibition may alter both acetylation and phosphorylation of viral proteins. Subsequently, cellular signaling pathways were reprogrammed and contributed to anti-tumor effects of SAHA in NPC cells.